2002
DOI: 10.1097/00002030-200203080-00004
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic analysis of plasma HIV-1 RNA after influenza vaccination of patients with previously undetectable viral loads

Abstract: Evidence is presented that supports the contention that a small subset of patients who experience viral load elevations after influenza vaccination can develop mutational changes in the RT region of the viral genome either acutely or after a failure of the viral load to return to undetectable levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 22 publications
0
23
1
1
Order By: Relevance
“…In the population with human immunodeficiency virus (HIV) infection, there is no general consensus on the effects of influenza vaccination on viral loads or CD4 counts [86,87]. Nevertheless, vaccination of HIV-positive individuals has been found to induce protective antibodies in both early and advanced HIV disease irrespective of CD4 counts.…”
Section: Prophylaxis and Infectionmentioning
confidence: 99%
“…In the population with human immunodeficiency virus (HIV) infection, there is no general consensus on the effects of influenza vaccination on viral loads or CD4 counts [86,87]. Nevertheless, vaccination of HIV-positive individuals has been found to induce protective antibodies in both early and advanced HIV disease irrespective of CD4 counts.…”
Section: Prophylaxis and Infectionmentioning
confidence: 99%
“…Antibodies (or CTL) will alter extracellular concentrations of Env proteins, thus changing intracellular envelope concentrations once extracellular /intracellular Env concentrations equilibrate. Therefore, antibodies to heterologous envelope proteins – developing, for example, during immunization against other viruses or heterotypic co-infection – will reduce relative intracellular concentrations of variant envelope, favouring RNA pol :Env Wt interactions, thus enhancing replication and increasing mutation rates, a prediction confirmed in practice [38,56]. Contrariwise, antibodies to wild-type surface proteins – for example, during administration of anti-HBsAb following liver transplantation for HBV [63] – would reduce viral replication (Figure 6), as seen in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined replication of HIV after immune stimulation with influenza vaccine or other antigens, noting viral load levels in blood and PBMCs and effects on lymphocyte subpopulation changes in peripheral blood [O'Brien et al, 1995;Glesby et al, 1996;Stanley et al, 1996;Kolber et al, 2002;Skiest and Machala, 2003]. Kolber et al [2002] reported that a small subset of patients had increased HIV loads following influenza vaccination and that these could be associated with mutational changes in the RT region of the HIV genome.…”
Section: Discussionmentioning
confidence: 99%
“…Kolber et al [2002] reported that a small subset of patients had increased HIV loads following influenza vaccination and that these could be associated with mutational changes in the RT region of the HIV genome. Similarly, Stanley et al [1996] reported that HIV levels rose transiently following stimulation with the recall antigen tetanus toxoid.…”
Section: Discussionmentioning
confidence: 99%